Imagens da morte: o artista diante do luto - Maria Portes Santana (2018)
The thesis presented here intends to penetrate the universe of images that express symbols, concepts, senses and meanings that surround death, consacrating the artist in face of grief. In order to do so, I propose a recalling of my history of facing the loss of my father, by sharing memories and feelings that came from that moment, in addition to the images named Death Marks produced by me during this work. I also recall the first artworks that portrayed death during Middle Age, from the years 400, in Western Europe, such as Ars Moriendi and Os Vers de La Mort, besides works that, even though belonging to other times such as The Frieze of Life, from Edvard Munch, created at the turning from the 19th century to the 20th, and the movie Cries and Whispers, from Ingmar Bergman, produced in 1972 continue to represent the relationship between man and death, and to make the analysis proposed by this research work possible.